Positive electrode material capable of reducing heat release of high-nickel ternary material and preparation method and application of positive electrode material

By combining high-nickel ternary materials with nano-scale inorganic materials to form a new positive electrode material, the problem of thermal runaway in lithium batteries is solved, and the effect of reducing heat exogenous energy and improving safety performance is achieved.

CN119812330APending Publication Date: 2025-04-11HEYUAN LICHUANG (SUZHOU) NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411901861.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

High-nickel ternary lithium batteries are prone to thermal runaway and fire accidents during use, and the prior art is difficult to effectively reduce their heat release.

Method used

By combining high-nickel ternary materials with nano-scale inorganic materials (such as Mg(OH)2 and Al(OH)3), a new positive electrode material is formed, and the flame retardant mechanism of inorganic materials is used to reduce heat exothermic.

Benefits of technology

It effectively reduces the heat release of lithium batteries, improves the safety performance of the battery, enhances the flame retardant performance, and reduces the possibility of fire accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812330A_ABST
    Figure CN119812330A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material capable of reducing heat release of a high-nickel ternary material and a preparation method and application thereof. Slurry of the positive electrode material comprises the following raw materials in parts by weight: 80-99 parts of the high-nickel ternary material, 1-20 parts of an inorganic material, 0.2-1.5 parts of a conductive agent, 0.5-3 parts of a binder and 20-50 parts of a solvent, the inorganic material comprises a solid electrolyte, phosphate, a metal hydroxide flame retardant, a halogen flame retardant, a phosphorus flame retardant, a silicon flame retardant and a boron flame retardant. According to the positive electrode material for reducing the heat release of the high-nickel ternary material and the preparation method and application thereof, the high-nickel ternary material and the inorganic flame retardant are compounded, the advantages of the material can be further synthesized, short-plate complementation is realized through compounding, the safety performance is improved on the premise that the energy density is not changed, the performance and the safety are both considered, and the positive electrode material is suitable for large-scale popularization and application. And the battery has more comprehensive and comprehensive battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode materials, and in particular relates to a positive electrode material capable of reducing the heat release of a high-nickel ternary material, and a preparation method and application thereof. Background Art

[0002] According to incomplete statistics, more than 60 fire accidents caused by battery energy storage systems have been reported in my country in the past 10 years. The safety importance of lithium batteries is self-evident. Thermal runaway of battery energy storage systems is the main safety issue of lithium batteries, and the main causes of thermal runaway of lithium batteries can be roughly divided into mechanical abuse, electrical abuse and thermal abuse. These abuses will eventually cause the collapse of the positive and negative electrodes, electrolytes, diaphragms and other structures of the battery, triggering complex chemical reactions, and ultimately leading to thermal runaway, resulting in casualties and property losses. Therefore, controlling the heat released during thermal runaway of the battery cell is the key to solving the problems of new energy vehicles, energy storage and new energy industries.

[0003] Therefore, the purpose of the present invention is to develop an electrode material and a preparation method thereof that can reduce the heat release of high-nickel ternary materials, which can be applied to lithium batteries to reduce the overall heat release of the positive electrode by mixing a safer inorganic material.

[0004] Inorganic flame retardants are abundant in resources, low in cost, low in toxicity, low in smoke, and environmentally friendly, and they even have a filling function. Magnesium hydroxide and aluminum hydroxide are non-toxic and smoke-suppressing, do not generate toxic smoke when decomposed, and have high thermal stability, making them popular inorganic flame retardants.

[0005] By combining high-nickel ternary materials with inorganic materials, the advantages of electrode materials can be further comprehensively enhanced, and the shortcomings can be complemented through compounding. Safety performance can be improved while the energy density remains unchanged, and the battery performance can be more comprehensive and integrated. Summary of the invention

[0006] Purpose of the invention: In order to overcome the above shortcomings, the purpose of the present invention is to provide a positive electrode material that reduces the heat release of high-nickel ternary materials, and its preparation method and application. The design is reasonable. By compounding high-nickel ternary materials with inorganic materials, the advantages of the materials can be further integrated, and the shortcomings can be complemented by compounding. The safety performance is improved under the premise of unchanged energy density, and both performance and safety are taken into account. When it is applied to lithium batteries, it has more comprehensive and integrated battery performance and has broad application prospects.

[0007] The objective of the present invention is achieved through the following technical solutions: A positive electrode material for reducing the heat release of a high-nickel ternary material, wherein the slurry of the positive electrode material comprises the following raw materials in parts by weight: 80-99 parts of high nickel ternary material; 1 to 20 parts of inorganic materials; the inorganic materials include solid electrolytes, phosphates, metal hydroxide flame retardants, halogen flame retardants, phosphorus flame retardants, silicon flame retardants, and boron flame retardants; Conductive agent 0.2-1.5 parts; 0.5-3 parts of binder; 20 to 50 parts of solvent.

[0008] In order to take into account both performance and safety, the present invention compounds high-nickel ternary materials with inorganic materials, which can further integrate the advantages of the materials and achieve complementary shortcomings through compounding.

[0009] Furthermore, in the above-mentioned positive electrode material for reducing the heat release of high-nickel ternary materials, the inorganic material is mixed in the slurry of the positive electrode material in a mass ratio of 2 to 10%.

[0010] Furthermore, the above-mentioned positive electrode material for reducing the heat release of the high-nickel ternary material, the high-nickel ternary material is a high-nickel nickel cobalt manganese oxide with a nickel content of more than 80%.

[0011] Furthermore, the above-mentioned positive electrode material that reduces the heat release of the high-nickel ternary material, the high-nickel ternary material is one or a combination of more of Ni80, Ni83, Ni88, Ni90, Ni91, Ni92, Ni93, and Ni95.

[0012] Furthermore, the above-mentioned positive electrode material for reducing the heat release of high-nickel ternary materials, the inorganic material is one or a combination of more of LATP, LLTO, LLZO, LMFP, LFP, Mg(OH)2, Al(OH)3, Zr(OH)2, Ca(OH)2, Sb2O3, Sb2O5, SiO2, ZB; the particle size of the inorganic material is 0.1~5um.

[0013] Preferably, the particle size of the inorganic material is 0.1 um.

[0014] The present invention adopts nano inorganic materials. Since nano inorganic material particles are smaller than micron inorganic material particles, the specific surface area is higher, the materials are more tightly bonded, and the carbon-forming performance of the materials is improved. In addition, when the lithium battery assembled with the material is improperly used such as overcharging and short circuit, the flame retardant mechanism of the nano particles is effectively used. The thermal decomposition of the nano particles will produce moisture, which will reduce the temperature of the lithium battery system, so that the battery safety of the lithium battery is effectively improved. At the same time, the addition of the material increases the thermal decomposition temperature of the positive electrode, so that the battery as a whole has better flame retardant performance, solves the safety problem of liquid batteries and reduces the possibility of dangerous accidents.

[0015] Furthermore, in the above-mentioned positive electrode material for reducing the heat release of high-nickel ternary materials, the conductive agent is one or a combination of conductive carbon black Super P, carbon nanotubes, acetylene black, and Ketjen black; the binder is polyvinylidene fluoride; and the solvent is nitrogen methyl pyrrolidone.

[0016] Preferably, the conductive agent is conductive carbon black Super P.

[0017] The present invention also relates to a method for preparing a positive electrode material that reduces the heat release of a high-nickel ternary material, comprising the following contents: in a dry room, firstly, mixing a high-nickel ternary material, an inorganic material, a conductive agent, and a binder in a homogenizing device, then adding a solvent, mixing into a uniform positive electrode slurry, and then coating the mixture on an aluminum foil current collector, baking at 60 to 120° C. for 5 to 16 hours under a vacuum state, and then taking out to obtain a positive electrode material.

[0018] Preferably, the baking is carried out at 100° C. for 5 hours under vacuum.

[0019] Furthermore, in the above-mentioned method for preparing the positive electrode material for reducing the heat release of the high-nickel ternary material, the environmental dew point should be controlled to ≤-40°C during the preparation process.

[0020] Furthermore, in the above-mentioned method for preparing a positive electrode material for reducing the heat release of a high-nickel ternary material, the compaction density of the positive electrode slurry is 2.3-3.5 g / cm 3 .

[0021] The present invention also relates to the application of the positive electrode material for reducing the heat release of the high-nickel ternary material, and the positive electrode material for reducing the heat release of the high-nickel ternary material is applied to lithium-ion batteries.

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) The positive electrode material for reducing the heat release of high-nickel ternary materials disclosed in the present invention is reasonably designed. By mixing a safer inorganic material to reduce the overall heat release of the positive electrode material, the high-nickel ternary material and the inorganic material are composited to further integrate the advantages of the materials. The composite material can complement each other's shortcomings, improve the safety performance under the premise of unchanged energy density, and have more comprehensive and integrated battery performance; the inorganic material is nano-scale, which shows better flame retardancy, because the nano-inorganic material particles are smaller than the micron inorganic material particles, have a higher specific surface area, and the materials are more tightly bonded, and the carbon-forming performance of the material is improved; (2) The method for preparing the positive electrode material for reducing the heat release of the high-nickel ternary material proposed in the present invention is simple and highly flexible, and has application prospects for large-scale industrial production; (3) The present invention proposes the application of positive electrode materials that reduce the heat release of high-nickel ternary materials. Lithium batteries assembled with this material can effectively utilize the flame retardant mechanism of inorganic materials in the event of improper use such as overcharging and short circuit. The thermal decomposition of this material will produce moisture, which will reduce the temperature of the lithium battery system and effectively improve the battery safety of the lithium battery. At the same time, the addition of inorganic materials increases the thermal decomposition temperature of the positive electrode, so that the lithium battery as a whole has better flame retardant properties, solving the safety problems of liquid batteries and reducing the possibility of dangerous accidents. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is the first-cycle discharge specific energy performance diagram of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention; Figure 2 This is a first-cycle capacity performance diagram of the electrical performance of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0024] The following will be attached Figure 1 , 2 In combination with Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 2, Example 3, Example 4, Example 5, Example 6, Example 7 and specific experimental data, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the protection scope of the present invention. The following Example 1, Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4, Comparative Example 5 and Example 2, Example 3, Example 4, Example 5, Example 6, and Example 7 provide a positive electrode material, a positive electrode sheet, a lithium battery, and a preparation method thereof for reducing the heat release of a high-nickel ternary material.

[0025] Example 1 The preparation of the positive electrode material and positive electrode sheet of Example 1 includes the following contents: in a dry room, the high-nickel ternary material Ni93, the inorganic material 0.1um Mg(OH)2, the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are mixed evenly in a slurry equipment in a mass ratio of 8.82:0.18:0.5:0.5 to obtain a positive electrode active material, and then 30wt% solvent nitrogen methyl pyrrolidone (NMP) is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and dried in a vacuum oven at 100°C for 5h, and after taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, placed in a vacuum dryer for standby use, and placed in a vacuum drying oven at 100°C for more than 1h before use.

[0026] The preparation of the lithium battery of Example 1 includes the following contents: In a glove box filled with argon atmosphere, a button CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of Example 1, 40 microliters of electrolyte, diaphragm, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0027] The first cycle capacity test results of the lithium battery of Example 1 are as follows: Figure 1 , 2 As shown by Figure 1 , 2 It can be seen that the lithium battery prepared in Example 1 has an excellent specific capacity at room temperature, which can reach 208.21 mAh / g, and the first efficiency is 86.51%.

[0028] The high nickel ternary material is compounded with the inorganic flame retardant Mg(OH)2, and its flame retardant mechanism is as follows: (1) Mg(OH)2 decomposes and absorbs heat. Mg(OH)2 decomposes to generate magnesium oxide (MgO). This process will cause the temperature of the system to drop, which can inhibit the temperature rise of the polymer and make it difficult for the polymer to be ignited.

[0029] (2) During the thermal decomposition process of Mg(OH)2, water will be generated, which will continue to absorb heat and become water vapor and release water vapor to the outside. These processes are accompanied by heat loss. At the same time, water vapor can also dilute flammable volatiles and oxygen, reducing their concentrations, thereby reducing the combustion intensity in the gas phase.

[0030] (3) MgO can form a metal oxide covering layer with high thermal stability through physical accumulation, which can prevent the volatilization and release of combustibles, prevent oxygen from entering the interior, and inhibit the oxidative decomposition of polymers; the MgO layer also has a certain adsorption capacity and can adsorb smoke, volatiles and free radicals generated during combustion, and deposit in the condensed phase to form a carbon layer, which can not only reduce the emission of dense smoke but also inhibit the decomposition of polymers, and has the characteristics of smoke suppression and low toxicity.

[0031] (4) Metal oxides also have certain catalytic abilities. When used in conjunction with other intumescent flame retardants, they can catalyze and promote the carbonization process of the flame retardant system and increase the amount of residual carbon. At the same time, MgO with high thermal stability dispersed in the carbon layer can also improve the heat resistance of the carbon layer.

[0032] Comparative Example 1 The preparation of the positive electrode material and positive electrode sheet of Comparative Example 1 includes the following contents: in a dry room, the high-nickel ternary material Ni93, the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are mixed evenly in a slurry equipment in a mass ratio of 9.0:0.5:0.5 to obtain a positive electrode active material, and then 30wt% of the solvent NMP is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and dried in a vacuum oven at 100°C for 6h. After taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, placed in a vacuum dryer for standby use, and placed in a vacuum drying oven at 100°C for more than 1h before use.

[0033] The preparation of the lithium battery of Comparative Example 1 includes the following contents: In a glove box filled with argon atmosphere, a button-type CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of Comparative Example 1, 40 microliters of electrolyte, diaphragm, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0034] The first cycle capacity test results of the lithium battery of Comparative Example 1 are as follows: Figure 1 , 2 As shown by Figure 1 , 2 It can be seen that the lithium battery prepared in this comparative example 1 has an excellent specific capacity at room temperature, which can reach 204.58 mAh / g, and the first efficiency is 87.08%.

[0035] Comparative Example 2 The preparation of the positive electrode material and positive electrode sheet of Comparative Example 2 includes the following contents: in a dry room, high nickel ternary material Ni93, inorganic material 0.1um Mg(OH)2, conductive agent carbon black Super P, and binder polyvinylidene fluoride are mixed evenly in a homogenization equipment in a mass ratio of 8.55:0.45:0.5:0.5 to obtain a positive electrode active material, and then 30wt% solvent NMP is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and dried in a vacuum oven at 100°C for 6h. After taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, put into a vacuum dryer for standby use, and then put into a vacuum drying oven at 100°C for more than 1h before use.

[0036] The preparation of the lithium battery of Comparative Example 2 includes the following contents: In a glove box filled with argon atmosphere, a button-type CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of Comparative Example 2, 40 microliters of electrolyte, diaphragm, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0037] The first cycle capacity test results of the lithium battery of Comparative Example 2 are as follows: Figure 1 , 2 As shown by Figure 1 , 2 It can be seen that the lithium battery prepared in Comparative Example 2 has an excellent specific capacity at room temperature, which can reach 194.2 mAh / g, and the first efficiency is 85.43%.

[0038] The lithium batteries of Example 1, Comparative Example 1 and Comparative Example 2 were subjected to DSC test. The DSC test data are shown in Table 1.

[0039] Table 1 DSC test data of lithium batteries of Example 1, Comparative Example 1 and Comparative Example 2 Onset endothermic temperature / ℃ Maximum endothermic temperature / ℃ <![CDATA[Heat release / J g -1 > Comparative Example 1 221.1 236.6 131.3 Example 1 223.4 237.3 111.0 Comparative Example 2 226.2 242.3 82.9 It can be seen from Table 1 that the initial endothermic temperature and the maximum endothermic temperature of the lithium batteries of Example 1 and Comparative Example 2 mixed with inorganic materials are increased, the time to reach the maximum reaction rate is prolonged, and the heat release is reduced, which shows that the compounding of high-nickel ternary materials with inorganic flame retardants can effectively inhibit the exothermic reaction inside the battery, delay the occurrence of thermal runaway to a certain extent, mitigate the consequences of thermal runaway, and improve the safety of the battery.

[0040] Comparative Example 3 The preparation of the positive electrode material and positive electrode sheet of Comparative Example 3 includes the following contents: in a dry room, high nickel ternary material Ni93, inorganic material 0.1um Al(OH)3, conductive agent carbon black Super P, and binder polyvinylidene fluoride are mixed evenly in a homogenization equipment in a mass ratio of 8.82:0.18:0.5:0.5 to obtain a positive electrode active material, and then 30wt% solvent NMP is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and dried in a vacuum oven at 100°C for 6h. After taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, placed in a vacuum dryer for standby use, and placed in a vacuum drying oven at 100°C for more than 1h before use.

[0041] The preparation of the lithium battery of comparative example 3 includes the following contents: in a glove box filled with argon atmosphere, a button-type CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of comparative example 3, 40 microliters of electrolyte, diaphragm, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0042] The first cycle capacity test results of the lithium battery of Comparative Example 3 are as follows: Figure 1 , 2 As shown by Figure 1 , 2It can be seen that the lithium battery prepared in Comparative Example 3 has an excellent specific capacity at room temperature, which can reach 201.12 mAh / g, and the first efficiency is 85.96%.

[0043] Comparative Example 4 The preparation of the positive electrode material and positive electrode sheet of Comparative Example 4 includes the following contents: in a dry room, high nickel ternary material Ni91, inorganic material 0.1um Al(OH)3, conductive agent carbon black Super P, and binder polyvinylidene fluoride are mixed evenly in a homogenization equipment in a mass ratio of 8.82:0.18:0.5:0.5 to obtain a positive electrode active material, and then 30wt% solvent NMP is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and dried in a vacuum oven at 100°C for 6h. After taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, put into a vacuum dryer for standby use, and then put into a vacuum drying oven at 100°C for more than 1h before use.

[0044] The preparation of the lithium battery of Comparative Example 4 includes the following contents: In a glove box filled with argon atmosphere, a button-type CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of Comparative Example 4, 40 microliters of electrolyte, diaphragm, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0045] Comparative Example 5 The preparation of the positive electrode material and positive electrode sheet of Comparative Example 5 includes the following contents: in a dry room, high nickel ternary material Ni93, inorganic material 0.1um Mg(OH)2, conductive agent carbon black Super P, and binder polyvinylidene fluoride are mixed evenly in a homogenization equipment in a mass ratio of 7.2:1.8:0.5:0.5 to obtain a positive electrode active material, and then 30wt% solvent NMP is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and dried in a vacuum oven at 100°C for 6h. After taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, put into a vacuum dryer for standby use, and then put into a vacuum drying oven at 100°C for more than 1h before use.

[0046] The preparation of the lithium battery of comparative example 5 includes the following contents: in a glove box filled with argon atmosphere, a button-type CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of comparative example 5, 40 microliters of electrolyte, diaphragm, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0047] Example 2 The preparation of the positive electrode material and positive electrode sheet of Example 2 includes the following contents: in a dry room, the high-nickel ternary material Ni93, the inorganic material 1um Mg(OH)2, the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are mixed evenly in a slurry equipment in a mass ratio of 8.82:0.18:0.5:0.5 to obtain a positive electrode active material, and then 30wt% solvent NMP is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and dried in a vacuum oven at 100°C for 6h. After taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, placed in a vacuum dryer for standby use, and placed in a vacuum drying oven at 100°C for more than 1h before use.

[0048] The preparation of the lithium battery of Example 2 includes the following contents: In a glove box filled with argon atmosphere, a button CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of Example 2, 40 microliters of electrolyte, diaphragm, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0049] Example 3 The preparation of the positive electrode material and positive electrode sheet of Example 3 includes the following contents: in a dry room, the high-nickel ternary material Ni91, the inorganic material 0.1um Mg(OH)2, the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are mixed evenly in a slurry equipment in a mass ratio of 8.82:0.18:0.5:0.5 to obtain a positive electrode active material, and then 30wt% solvent NMP is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and baked in a vacuum oven at 100°C for 6h. After taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, put into a vacuum dryer for standby use, and then put into a vacuum drying oven at 100°C for more than 1h before use.

[0050] The preparation of the lithium battery of Example 3 includes the following contents: In a glove box filled with argon atmosphere, a button CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of Example 3, 40 microliters of electrolyte, separator, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0051] Example 4 The preparation of the positive electrode material and positive electrode sheet of Example 4 includes the following contents: in a dry room, the high nickel ternary material Ni93, the inorganic material 0.1um LATP, the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are mixed evenly in a slurry equipment in a mass ratio of 8.82:0.18:0.5:0.5 to obtain a positive electrode active material, and then 30wt% solvent NMP is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and dried in a vacuum oven at 100°C for 6h, and after taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, put into a vacuum dryer for standby use, and then put into a vacuum drying oven at 100°C for more than 1h before use.

[0052] The preparation of the lithium battery of Example 4 includes the following contents: In a glove box filled with argon atmosphere, a button CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of Example 4, 40 microliters of electrolyte, diaphragm, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0053] Example 5 The preparation of the positive electrode material and positive electrode sheet of Example 5 includes the following contents: in a dry room, the high-nickel ternary material Ni93, the inorganic material 0.1um LMFP, the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are mixed evenly in a slurry equipment in a mass ratio of 8.82:0.18:0.5:0.5 to obtain a positive electrode active material, and then 30wt% solvent NMP is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and baked in a vacuum oven at 100°C for 6h, and after taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, put into a vacuum dryer for standby use, and then put into a vacuum drying oven at 100°C for more than 1h before use.

[0054] The preparation of the lithium battery of Example 5 includes the following contents: In a glove box filled with argon atmosphere, a button CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of Example 5, 40 microliters of electrolyte, diaphragm, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0055] Example 6 The preparation of the positive electrode material and positive electrode sheet of Example 6 includes the following contents: in a dry room, the high nickel ternary material Ni93, the inorganic material 0.1um LATP, 0.1um LMFP, the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are mixed evenly in a homogenization equipment in a mass ratio of 8.1:0.63:0.27:0.5:0.5 to obtain a positive electrode active material, and then 30wt% solvent NMP is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and dried in a vacuum oven at 100°C for 6h. After taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, put into a vacuum dryer for standby use, and then put into a vacuum drying oven at 100°C for more than 1h before use.

[0056] The preparation of the lithium battery of Example 6 includes the following contents: In a glove box filled with argon atmosphere, a button CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of Example 6, 40 microliters of electrolyte, diaphragm, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0057] Example 7 The preparation of the positive electrode material and positive electrode sheet of Example 7 includes the following contents: in a dry room, the high nickel ternary material NCM811, the inorganic material 0.1um Mg(OH)2, the conductive agent carbon black Super P, and the binder polyvinylidene fluoride are mixed evenly in a slurry equipment in a mass ratio of 8.82:0.18:0.5:0.5 to obtain a positive electrode active material, and then 30wt% solvent NMP is added, mixed into a uniform slurry and coated on an aluminum foil current collector, and dried in a vacuum oven at 100°C for 6h. After taking out, the positive electrode material is obtained; the above-mentioned positive electrode material is cut into a disc-shaped electrode (positive electrode sheet) with a diameter of 12mm, put into a vacuum dryer for standby use, and then put into a vacuum drying oven at 100°C for more than 1h before use.

[0058] The preparation of the lithium battery of Example 7 includes the following contents: In a glove box filled with argon atmosphere, a button CR2032 battery is used for testing. The battery is assembled in the manner of positive electrode shell, positive electrode sheet of Example 7, 40 microliters of electrolyte, diaphragm, 40 microliters of electrolyte, metal lithium sheet, gasket, spring, negative electrode shell. The assembled lithium battery is left at 25°C for 12 hours.

[0059] As can be seen from the above, the present invention provides an effective method for reducing the heat release of high-nickel ternary materials and the preparation of electrodes. By adding nano-scale inorganic materials to high-nickel ternary materials, better flame retardancy can be exhibited, and the lithium battery assembled using the positive electrode material can effectively utilize the flame retardant mechanism of nano-inorganic material particles in the case of improper use such as overcharging and short circuit. The thermal decomposition of the nano-inorganic material particles will produce moisture, which will reduce the temperature of the lithium battery system and effectively improve the battery safety of the lithium battery. At the same time, the addition of the nano-scale inorganic material increases the thermal decomposition temperature of the positive electrode, so that the lithium battery as a whole has better flame retardant properties, solves the safety problems of liquid batteries and reduces the possibility of dangerous accidents. The preparation method is simple and has application prospects for large-scale industrial production.

[0060] The present invention has many specific application paths, and the above is only a preferred embodiment of the present invention. It should be pointed out that the above embodiments are only used to illustrate the present invention, and are not used to limit the protection scope of the present invention. For those of ordinary skill in the art, several improvements can be made without departing from the principle of the present invention, and these improvements should also be regarded as the protection scope of the present invention.

Claims

1. A positive electrode material for reducing the heat release of high-nickel ternary materials, characterized in that: The slurry of the positive electrode material includes the following raw materials in parts by weight: 80-99 parts of high nickel ternary material; 1 to 20 parts of inorganic materials; the inorganic materials include solid electrolytes, phosphates, metal hydroxide flame retardants, halogen flame retardants, phosphorus flame retardants, silicon flame retardants, and boron flame retardants; Conductive agent 0.2-1.5 parts; 0.5-3 parts of binder; 20 to 50 parts of solvent.

2. The positive electrode material for reducing the heat release of high-nickel ternary materials according to claim 1, characterized in that: The inorganic material is mixed in the positive electrode material slurry in a mass ratio of 2 to 10%.

3. The positive electrode material for reducing the heat release of high-nickel ternary materials according to claim 1, characterized in that: The high-nickel ternary material is high-nickel nickel cobalt lithium manganese oxide with a nickel content of more than 80%.

4. The positive electrode material for reducing the heat release of high-nickel ternary materials according to claim 1, characterized in that: The high-nickel ternary material is one or a combination of more of Ni80, Ni83, Ni88, Ni90, Ni91, Ni92, Ni93, and Ni95.

5. The positive electrode material for reducing the heat release of high-nickel ternary materials according to claim 1, characterized in that: The inorganic material is one or a combination of LATP, LLTO, LLZO, LMFP, LFP, Mg(OH)2, Al(OH)3, Zr(OH)2, Ca(OH)2, Sb2O3, Sb2O5, SiO2, and ZB; the particle size of the inorganic material is 0.1 to 5 um.

6. The positive electrode material for reducing the heat release of high-nickel ternary materials according to claim 1, characterized in that: The conductive agent is one or a combination of conductive carbon black Super P, carbon nanotubes, acetylene black, and Ketjen black; the binder is polyvinylidene fluoride; and the solvent is nitrogen methyl pyrrolidone.

7. The method for preparing a positive electrode material for reducing the heat release of a high-nickel ternary material according to any one of claims 1 to 6, characterized in that: The method includes the following contents: in a dry room, firstly, high nickel ternary material, inorganic material, conductive agent and binder are uniformly mixed in a slurry device, then solvent is added, mixed into a uniform positive electrode slurry and then coated on an aluminum foil current collector, and then baked at 60-120° C. for 5-16 hours under vacuum state and taken out to obtain the positive electrode material.

8. The method for preparing a positive electrode material for reducing the heat release of a high-nickel ternary material according to claim 7, characterized in that: During the preparation process, the ambient dew point should be controlled at ≤-40℃.

9. The method for preparing a positive electrode material for reducing the heat release of a high-nickel ternary material according to claim 7, characterized in that: The compaction density of the positive electrode slurry is 2.3-3.5 g / cm 3 .

10. Use of the positive electrode material for reducing the heat release of high-nickel ternary materials according to any one of claims 1 to 6 in the preparation of lithium-ion batteries.